TO A QUESTION OF DETERMINATION OF HYDRAULIC RADIUS OF A BACKFILL FLOW FOR THE EXCENTRATIVE PLACEMENT OF PIPES IN DRILLING BORE - Moishyshyn, V. M.; Biletskii, Y. S.; Vryukalo, V. V.; Seniushkovych, M. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2018)
The processes of displacement of drilling clay backfill flow from the intertubular space formed by internal surface of external and external surfaces of inner tubes are considered. In case of eccentric placement of pipes it is proposed in the form of a cross-section of the flow of a backfill to take the area limited from the outside by the Pascal's snail, and from the inside - the outer surface of the inner pipe at the first time. The formulas for determining areas of the cross section of the flow and the stagnant zone, the perimeter and the hydraulic radius of the section of the flow for the eccentric placement of the pipes in the bore are proposed. The dimensionless parameter α is introduced as the ratio of the centripetal distance to difference between internal radius of outer pipe and outer radius of inner tube. It was found that with increasing of α cross-sectional area and their hydraulic radii are increasing, and the area of stagnant zones decreases according to parabolic laws. It is established that with the growth of α velocity of the backfill flow decreases according to parabolic laws and their values are in good agreement with the experimental data.